The Effect of Risk Control Techniques on Organisational Performance of Selected SMES in Lagos State: Array - Ajemunigbohun, Sunday (Acta Universitatis Danubius. Œconomica, 2022)
The aim of the study is to evaluate the effect of risk control techniques on organisational performance of selected SMEs in Lagos State. The specific objectives are to consider the effect of physical risk and financial control techniques on organisational performance of selected SMEs in Lagos State, Nigeria. The study is limited to the effect of risk control techniques on the performance of SMEs in Lagos State, Nigeria. The precise variables of interest are the physical risk control techniques which are risk elimination and risk reduction as well as the financial risk control techniques which focus on risk retention and risk transfer. The study covers 10 major clustered markets in Lagos State where there are selected SMEs ranging from Oil and gas, manufacturing companies, service companies, and general merchandise in Lagos State. The study employed a survey research design and adopted a convenience sampling method of selection and a multi clustered method was used in selection. A survey monkey was used to administer the questionnaire to the sampled respondents. The hypothesis was tested using regression analysis through the use of SPSS and the results showed that there is a positive and significant correlation. relation and effect of physical and financial risk control on organisational performance of selected SMEs. It was concluded that SMEs should embrace all efficient and economic means to address the potential risk that can threaten their existence.it was recommended that SMEs should increase its risk appetite to enhance efficient management of their business.